KEGIATAN STORYTELLING DALAM PENINGKATKAN KETERAMPILAN BERBAHASA ANAK DI PERPUSTAKAAN KOBER AL-QOLAM - Iqbal Kesuma; Rifqi Zaeni Achmad Syam; Oom Nurrohmah (Nusantara Journal of Information and Library Studies (N-JILS), 2022)
This study aims to determine the application of storytelling activities in improving the language skills of children aged 5 to 6 years at the Kober Al-Qolam Library Bandung which is seen from the listening aspect, speaking aspect, writing aspect and reading aspect. This research is a qualitative descriptive study involving teachers and principals. Data were collected through interviews, observation and document analysis. Data analysis through data collection, data reduction, data presentation and drawing conclusions. The results showed that the application of storytelling activities was able to improve language skills in Kober Al-Qolam. This can be seen in several aspects, namely in the listening aspect, which occurs when the teacher is able to attract children's attention when telling stories. In the speaking aspect, it occurs when the teacher provides a stimulus in the form of questions to the child and the child can answer the teacher's question. As for the writing aspect and the reading aspect, it occurs when the teacher gives orders to the child to write the character in the story, for example when asked to write the name of the character "Kancil". At preschool age children they are still in the early writing and reading stages, so they are not yet able to write complex sentences, but by giving orders to write the word "Deer" can improve early writing skills for children, after children recognize letters children can be taught to spell words so that it is able to improve reading skills in children. The obstacles in the implementation of this storytelling activity, namely the limitations of teaching aids, less varied and poorly maintained media, the lack of the latest reading books that can be used in storytelling, the limited mastery of storytelling methods by storytellers, and children in Kober Al-Qolam classified as children. at an early age (5-6 years), so that learning needs the role of parents to be maximized. Keywords: storytelling, language skills, early childhood educationABSTRAKPenelitian ini bertujuan untuk mengetahui penerapan kegiatan storytelling dalam peningkatan kemampuan berbahasa anak usia 5 hingga 6 tahun di Perpustakaan Kober Al-Qolam Bandung yang dilihat dari aspek menyimak, aspek berbicara, aspek menulis dan aspek membaca. Penelitian ini merupakan penelitian deskriptif kualitatif yang melibatkan guru dan kepala sekolah. Data dikumpulkan melalui wawancara, observasi dan analisis dokumen. Analisis data melalui pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan, bahwa penerapan kegiatan storytelling mampu meningkatkan keterampilan berbahasa di Kober Al-Qolam. Hal ini dapat dilihat pada beberapa aspek, yaitu pada aspek menyimak yaitu terjadi pada saat guru mampu menarik perhatian anak saat bercerita. Pada aspek berbicara yaitu terjadi pada saat guru memberikan stimulus berupa pertanyaan kepada anak dan anak dapat menjawab pertanyaan guru. Adapun pada aspek menulis dan aspek membaca, yaitu terjadi pada saat guru memberikan perintah kepada anak untuk menulis tokoh dalam cerita, contohnya ketika diminta menuliskan nama tokoh “Kancil”. Pada anak usia Paud mereka masih dalam tahap menulis dan membaca awal, sehingga belum mampu menulis kalimat yang kompleks, namun dengan memberikan perintah untuk menulis kata “Kancil” mampu meningkatkan keterampilan menulis permulaan bagi anak, setelah anak mengenal huruf anak bisa diajarkan untuk mengeja kata sehingga itu mampu meningkatkan keterampilan membaca pada anak. Adapun hambatan dalam pelaksanaan kegiatan storytelling ini, yaitu keterbatasan alat peraga, media yang kurang variatif dan kurang terawat, kurangnya buku bacaan terbaru yang bisa digunakan materi dalam bercerita, keterbatasan penguasaan metode bercerita oleh storyteller, dan anak yang berada di Kober Al-Qolam tergolong anak usia dini (5-6 tahun), sehingga pembelajarannya perlu adanya peran orang tua agar maksimal.